Dissonances of Existence and the living well: about the neoliberal advance and the new challenges of the new agenda in Contemporary Pedagogy (Praxis Educativa, 2019)
This article discusses the advance of neoliberalism, understood as the political imposition of a certain global pattern of power that constantly requires that the “dominated and defeated gazes” of those groups that suffer the effects of exclusion, naturalize and even justify these impositions and policies as well. That is why we will address the concept of dissonances of Existence to describe the ways of social anguish generated by this political rationality. In this regard we will start with a sort of genealogical analysis relative to these forms of cultural, social and emotional diaspora, that threaten the “Good Living” (or Living Well) of our peoples. Planning hope from a located pedagogy, understood as a cultural policy that gives voice to the voiceless ones, will constitute the main aim for the new agenda of contemporary pedagogy.
Keywords: neoliberalism; dissonances; existence; living well; pedagogy